ANALYSIS OF STUDENTS' SOCIALLY ACTIVE CITIZEN COMPETENCE REFLECTED IN NORMAL LEGAL DOCUMENTS AND ITS COMPOSITE STRUCTURE (Conferencea, 2022)
In our study, a theoretical analysis (articles, rules) of a number of normative legal documents of the Republic of Uzbekistan was conducted in order to justify the urgent need for the formation of socially active civic competence in high school students in the "Fundamentals of State and Law" classes. As a result, normative legal documents (laws, decrees, decisions) were determined, in which chapters and clauses define the content of "socially active citizenship competence", as well as the development and application of innovative pedagogical technologies in general education schools for the formation of this competence in the "Basics of State and Law" classes. there is.